Revitalizing Religious and Cultural Harmony through Prophetic Art: A Study of Gelaran Parowulan in Tegal - Zaman, M. Badruz; Azmi, M. Faiq (JURNAL INDO-ISLAMIKA, 2024)
This study explores the Gelaran Parowulan as a manifestation of prophetic art that integrates religious, cultural, and socio-political expressions in Tegal, Indonesia. Using a descriptive phenomenological approach, the research examines how this grassroots movement employs traditional art forms—such as poetry, puppetry, and dance—to convey Islamic values while addressing societal challenges. The findings highlight three key aspects: the socio-political critique inherent in performances, the aesthetic expression of religious experiences, and the embodiment of Islam's spirit of raḥmatan li al-‘ālamīn (mercy to all creation). Gelaran Parowulan not only revitalizes local art forms but also fosters inclusivity and solidarity among diverse communities. By rejecting formalism and promoting sincere engagement, this movement redefines da'wah as a dynamic, creative, and accessible practice. The study underscores the transformative potential of prophetic art in fostering harmony and addressing contemporary social issues.